Exploration of the Indonesian Makassar-Buginese Siri’ educational values: The foundation of character education - Asham Bin Jamaluddin; Siti Zubaidah; Susriyati Mahanal; Abdul Gofur (International Journal of Evaluation and Research in Education (IJERE), 2022)
Character is a crucial aspect of living in society. Character building has been carried out in Indonesia from hundred years ago. The people have improved their way of life by adopting local culture's educational values, such as the Makassar-Buginese Siri’. However, in this era, there is a deterioration of student character as a result of losing Siri' cultural ideals that are rarely found in the field of education. The study aimed to explore the Makassar-Buginese Siri’ educational values as the foundation of character building. This study was designed as a qualitative study using the ethno-pedagogy approach. The data were collected through interviews, observation, and documentation and analyzed through data reduction, data display, and conclusion drawing. The results have revealed that the Makassar-Buginese Siri’ contains the following educational values: teppe (faith), pesse (compassion), lempuk (honesty, straightening deeds, and intentions), sipakatau (humanizing human), sipakalebbi (glorification of human), sipakainge (reminding each other), sipatokkong (mutual help and mutual support), tongeng (sincerity), reso (hard work), and abbulosibatang (collaboration). In conclusion, the Makassar-Buginese Siri’ educational values play a crucial role in character education to be integrated into the learning process to improve student character.